Toxic timescapes examining toxicity across time and space - Müller, Simone M. 1982-; Nielsen, May-Brith Ohman 1962- (Ohio University Press, 2023)
"From radioactive waste to coral reefs, this environmental humanities volume reconsiders contamination and pollution as toxic timescapes: dynamic events with both temporal and spatial dimensions"--
Includes bibliographical references and index
Keywords: Pollution / History; Human ecology; Toxicology; Aufsatzsammlung